Morphometric, meristic and growth patterns of Belontia hasseltifrom the Banjiran Swamp, Air Hitam River, Payung Sekaki District, Riau Province - Fajar Malini; Ridwan Manda Putra; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractBelontia hasselti is a typeof freshwater fish that inhabit swamp waters.Information on biological, including morphometric, meristic, and growth patterns of the fish is rare. To understand the morphometrical andmeristicalcharacteristics, and growth patterns of the fish, a research had been conducted from February to March 2018. There were 100 fishes (70.08-130.05 mm TL and 7.44-40.02 gr BW). There were 26 morphological characteristics measured and 11 meristical characteristics counted. The meristical characteristics were as follows: D. XVI-XVII, 10-13 P.10-12,   V.I, 4-6 A. XV-XVII, 11-13). The number of scale in the pre-dorsal fin was 22-24, in the cheek was 4-6, around the body was 32-42,  in the caudal peduncle was 14-16, above lateral line was 4.5-6.5 and under lateral line was 11.5-13.5). There were 5 morphometrical characteristic differences between male and female B.hasselti.They wereheight of the head,  space from aye to the dorsal fin, space from ventral fin to the anal fin, the height of dorsal and the height of anal.The length-weight relationship shown that the growth of male and female was allometric negative.Keywords:freshwater fish, allometric, morphological characteristic, meristic characteristic